Jogo Tonggo Program Policy Innovation In Handling Covid-19 In Central Java Province - Charis Christiani; R Permadi Mulajaya (Universitas Pendidikan Ganesha, 2023)
Policy innovation in handling Covid-19 was carried out by the Central Java Provincial Government by issuing Instruction No. 1 of 2020 on Community Empowerment in Accelerating Covid-19 Handling at the Rukun Warga (RW) level by forming the Jogo Tonggo Task Force. The Jogo tonggo Task Force is a task force to maintain neighbors with ensuring that residents work together against the spread and transmission of Covid-19 in their regions, ensuring support from outside to fight targeted and appropriate. Purpose of the study is to analyze the Policy Innovation of Jogo Tonggo Program in Covid-19 Management in Central Java Province. The research methodology used is a descriptive research method with qualitative data analysis. The results showed that formation of the Jogo Tonggo Task Force in Central Java Provincial Government is a quick initiative in solving public problems. Through this program, the Central Java Government wants to deal with the Covid-19 pandemic with maintaining local wisdom. The Distribution of tasks of the Jogo Tonggo Task Force is the key to implementing policy innovations consisting of health, economic fields, social and security fields and entertainment. In addition, the Jogo Tonggo Task Force is part of efforts to solve the Covid-19 pandemic by involving the public. The concept of Jogo Tonggo Task Force involving all elements of society includes religious leaders / public leaders, publics, Village Health Polyclinic staff, Puskesmas and Posyandu.